Biofilm formation and inflammatory potential of Staphylococcus saccharolyticus: A possible cause of orthopedic implant-associated infections - Afshar, Mastaneh; Møllebjerg, Andreas; Minero, Gabriel Antonio; Hollensteiner, Jacqueline; Poehlein, Anja; Himmelbach, Axel; Lange, Jeppe; Meyer, Rikke Louise; Brüggemann, Holger (Frontiers in Microbiology, 2022)
Staphylococcus saccharolyticus, a coagulase-negative staphylococcal species, has some unusual characteristics for human-associated staphylococci, such as slow growth and its preference for anoxic culture conditions. This species is a relatively abundant member of the human skin microbiota, but its microbiological properties, as well as the pathogenic potential, have scarcely been investigated so far, despite being occasionally isolated from different types of infections including orthopedic implant-associated infections. Here we investigated the growth and biofilm properties of clinical isolates of S. saccharolyticus and determined host cell responses. Growth assessments in anoxic and oxic conditions revealed strain-dependent outcomes, as some strains can also grow aerobically. All tested strains of S. saccharolyticus were able to form biofilm in a microtiter plate assay. Strain-dependent differences were determined by optical coherence tomography, revealing that medium supplementation with glucose and sodium chloride enhanced biofilm formation. Visualization of the biofilm by confocal laser scanning microscopy revealed the role of extracellular DNA in the biofilm structure. In addition to attached biofilms, S. saccharolyticus also formed bacterial aggregates at an early stage of growth. Transcriptome analysis of biofilm-grown versus planktonic cells revealed a set of upregulated genes in biofilm-embedded cells, including factors involved in adhesion, colonization, and competition such as epidermin, type I toxin-antitoxin system, and phenol-soluble modulins (beta and epsilon). To investigate consequences for the host after encountering S. saccharolyticus, cytokine profiling and, host cell viability, and intracellular bacterial survival were assessed by infection experiments with differentiated THP-1 cells. The microorganism strongly triggered the secretion of the tested pro-inflammatory cyto- and chemokines IL-6, IL-8, and TNF-alpha determined at 24 h post-infection. S. saccharolyticus survived at least for 24 h intracellularly in differentiated THP-1 cells and was less cytotoxic than Staphylococcus aureus. Taken together, the results indicate that S. saccharolyticus has substantial pathogenic potential. Thus, it can be a potential cause of orthopedic implant-associated infections and other types of deep-seated infections.